2010
DOI: 10.1182/blood-2010-03-275438
|View full text |Cite
|
Sign up to set email alerts
|

Transient and persistent effects of IL-15 on lymphocyte homeostasis in nonhuman primates

Abstract: Interleukin-15 (IL-15) is a cytokine with potential therapeutic application in individuals with cancer or immunodeficiency to promote natural killer (NK)-and T-cell activation and proliferation or in vaccination protocols to generate long-lived memory T cells.Here we report that 10-50 g/kg IL-15 administered intravenously daily for 12 days to rhesus macaques has both short-and longlasting effects on T-cell homeostasis. Peripheral blood lymphopenia preceded a dramatic expansion of NK cells and memory CD8 T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 39 publications
5
104
0
Order By: Relevance
“…Non-human primate studies have recently shown that IL-15 administration expands memory CD8 ( þ ) and CD4 ( þ ) T, and NK cells in the peripheral blood. 27,32 Early-phase clinical studies are also underway. We believe that IL-15 will have an important role in immunotherapy, especially in improving post-transplant T-cell deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Non-human primate studies have recently shown that IL-15 administration expands memory CD8 ( þ ) and CD4 ( þ ) T, and NK cells in the peripheral blood. 27,32 Early-phase clinical studies are also underway. We believe that IL-15 will have an important role in immunotherapy, especially in improving post-transplant T-cell deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…16 Either fresh (BAL, LN, and Jej samples) or frozen (PBMC) cells were used for phenotyping and stimulation. PBMCs were frozen in FBS ϩ 10% DMSO and stored in liquid phase nitrogen until analysis.…”
Section: Isolation Of Mnc From Blood and Tissuesmentioning
confidence: 99%
“…In contrast, IL-15 alone did not have any effect on the level of CD8 ϩ T-cell activation ( Figure 1B). The expression of CD38 was also investigated and was found to be up-regulated by IL-15 therapy in multiple CD8ϩ T-cell memory subsets, 16 and could thus not be considered a reliable marker of the effect of ART on T-cell activation (data not shown).…”
Section: Il-15 Delays But Does Not Abrogate Art Mediated Suppression mentioning
confidence: 99%
See 2 more Smart Citations